Visual Storytelling and Design Analysis of “Sengoku BASARA” as a History-Based Game for the Implementation of Interest to the History - Jasmine Nuraliva Hanata; Yanuar Rahman; Patra Aditia (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Historical video games are one of the entertainment screen media genres that represent actual historical events influencing the players to learn interactively. Moreover, in an era where technology is increasingly advanced the presence of pop culture that is included in history-based games leads people to get interested more in things that were initially boring to follow. “Sengoku BASARA” (戦国BASARA) is a successful action game featuring a main character based on Japanese feudal warlords wrapped in fictional and dramatic form published by CAPCOM which is very popular in Japan. Yet, Indonesia hasn’t developed a game based on the history of their ancient kingdom with good qualities to bring their interest to learning. The research methodology in this study using a qualitative approach includes content analysis using the 5 W 1 H technique to explore how the historical events and characters in the game are visualized and how it brings or gives the player an understanding of the history. This study aims to delve into two main points: 1. Understanding how “Sengoku BASARA” adapts the elements of their history, 2. The potential of this game as an educational tool is to introduce the historical characters as well as their story events. In conclusion, “Sengoku BASARA” does not have perfect accuracy in visualizing the original history yet it can be the first step to learning more about history interestingly and entertainingly.